SCIENTIFIC-PEDAGOGICAL BASIS OF IMPROVING THE THEORETICAL BASIS OF USING TESTOLOGY IN THE EDUCATIONAL SYSTEM (Scientific journal of the Fergana State University, 2024)
In this article, it is proposed to take into account many factors when assessing students' educational achievements, as well as to take into account the socio-pedagogical environment and conditions. Today, the need to modernize pedagogical dimensions in education and the introduction of international programs is increasing in education. The main purpose of international assessment programs is to express opinions about the status of students' application of the knowledge they study at school in everyday life.